Are Examiners' Judgments in OSCE-Style Assessments Influenced by Contrast Effects?. (July 2015) - Yeates, Peter; Moreau, Marc; Eva, Kevin
Abstract : Purpose: Laboratory studies have shown that performance assessment judgments can be biased by "contrast effects." Assessors' scores become more positive, for example, when the assessed performance is preceded by relatively weak candidates. The authors queried whether this effect occurs in real, high-stakes performance assessments despite increased formality and behavioral descriptors. Method: Data were obtained for the 2011 United Kingdom Foundational Programme clinical assessment and the 2008 University of Alberta Multiple Mini Interview. Candidate scores were compared with scores for immediately preceding candidates and progressively distant candidates. In addition, average scores for the preceding three candidates were calculated. Relationships between these variables were examined using linear regression. Results: Negative relationships were observed between index scores and both immediately preceding and recent scores for all exam formats. Relationships were greater between index scores and the average of the three preceding scores. These effects persisted even when examiners had judged several performances, explaining up to 11% of observed variance on some occasions. Conclusions: These findings suggest that contrast effects do influence examiner judgments in high-stakes performance-based assessments. Although the observed effect was smaller than observed in experimentally controlled laboratory studies, this is to be expected given that real-world data lessen the strength of the intervention by virtue of less distinct differences between candidates. Although it is possible that the format of circuital exams reduces examiners' susceptibility to these influences, the finding of a persistent effect after examiners had judged several candidates suggests that the potential influence on candidate scores should not be ignored.